Land cover distribution in the peatlands of Peninsular Malaysia, Sumatra and Borneo in 2015 with changes since 1990 - Miettinen, Jukka; Shi, Chenghua; Liew, Soo Chin (Global ecology and conservation, 2016)
Insular Southeast Asian peatlands have experienced rapid land cover changes over the past decades inducing a variety of environmental effects ranging from regional consequences on peatland ecology, biodiversity and hydrology to globally significant carbon emissions. In this paper we present the land cover and industrial plantation distribution in the peatlands of Peninsular Malaysia, Sumatra and Borneo in 2015 and analyse their changes since 1990. We create the 2015 maps by visual interpretation of 30 m resolution Landsat data and combine them with fully comparable and completed land cover maps of 1990 and 2007 (Miettinen and Liew, 2010). Our results reveal continued peatland deforestation and conversion into managed land cover types. In 2015, 29% (4.6 Mha) of the peatlands in the study area remain covered by peat swamp forest (vs. 41% or 6.4 Mha in 2007 and 76% or 11.9 Mha in 1990). Managed land cover types (industrial plantations and small-holder dominated areas) cover 50% (7.8 Mha) of all peatlands (vs. 33% 5.2 Mha in 2007 and 11% 1.7 Mha in 1990). Industrial plantations have nearly doubled their extent since 2007 (2.3 Mha; 15%) and cover 4.3 Mha (27%) of peatlands in 2015. The majority of these are oil palm plantations (73%; 3.1 Mha) while nearly all of the rest (26%; 1.1 Mha) are pulp wood plantations. We hope that the maps presented in this paper will enable improved evaluation of the magnitude of various regional to global level environmental effects of peatland conversion and that they will help decision makers to define sustainable peatland management policies for insular Southeast Asian peatlands.